Examining brand equity and tourists’ purchasing motivations towards the world’s best rice ‘ST25’ for Vietnam’s future sustainable food tourism destination - Hoang, Cuu Long; Pham, Xuan Quyet (Journal of Finance - Marketing Research, 2023)
Until now, Vietnam is still confused about choosing a national product to represent the country and turning them into souvenirs everyone craves when traveling here. With the wide range of agricultural products, i.e., the world’s best in 2019 Rice ST25, Vietnam can leverage its advantages to create a suitable must-buy item for tourists. There are two primary purposes: (1) to identify the awareness of tourists about ST25 Rice and (2) to examine the ST25 Rice in Customers’ based brand equity (CBBE) model and purchasing motivations, therefore sustaining the tourism industry in the future. The study is done with quantitative research by a sample of 243 respondents who are from different countries staying in Ho Chi Minh City. The results show that rice ST25 is acknowledged, and consumers highly rate it, and its potential to be made into national gifts and to stand firm to represent the image of Vietnam from a tourism perspective. The conclusion and recommendations can be utilized to identify other hand-made items for Vietnam’s sustainable tourism.